DEVELOPING ENGLISH FOR CULINARY BOOK FOR ELEVENTH GRADE STUDENTS AT SMKS PARIWISATA TRIATMAJAYA SINGARAJA - Resaldi, Muhamad Ridho; Ratminingsih, Ni Made; Kusuma, I Putu Indra (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
This study aimed to develop an English for culinary book for eleventh-grade students at SMKS Pariwisata Triatma Jaya Singaraja. The type of this research is Research and Development using the ADDIE model by Branch (2009). This model is perceived to be more reasonable and complete during product development processes. There were 5 phases to carry out the study, including Analysis, Design, Development, Implementation, and Evaluation. The subject of this study was eleventh-grade students majoring in culinary arts at SMKS Pariwisata Triatma Jaya Singaraja, Bali. The researcher in this study also applied the theory of layout principles, which helped the researcher designed the cover and each material on each page in the book to be better organized and attractive. The research instruments used were an interview guide, questionnaire, document analysis, and checklist. This study showed that the product developed was categorized as very good and valued by two expert judges in some aspects. The users valued the product positively, in this case, the eleventh-grade student majoring in culinary at SMKS Pariwisata Triatma Jaya.